2008
DOI: 10.1002/jcla.20218
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin‐18 gene polymorphism with asthma in Chinese patients

Abstract: Like other allergic diseases, asthma results from multiple conditions. Asthmatic beginning and severity are mediated by both environmental and genetic factors. In asthma studies, important work is realization of the genetic background and identification of genetic factors resulting in asthma development and phenomena. Here, we investigated whether interleukin (IL)-18 single nucleotide polymorphisms (SNPs) are involved in Chinese asthma patients. IL-18 (IL-18) SNP was detected by polymerase chain reaction (PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Among them, Ϫ607 A/C (rs1946518), Ϫ137 C/G (rs187238) in the promoter region, and Ϫ140 C/G (previously Ϫ133 C/G, rs4988359) in intron 1 have been studied in detail with respect to etiopathogenesis of allergic diseases [15][16][17][18] and transcriptional activity or IL-18 production by monocytes [19 -21]. Current results have indicated the inconsistent association between IL-18 gene variants and clinical/ intermediary phenotypes of allergy in different populations [15][16][17][18][22][23][24][25][26][27][28][29][30][31]. However, a novel putative functional variant Ϫ1297 C/T (rs360719) within the IL-18 promoter region that seems to have an important role in IL-18 expression was recently associated with susceptibility to SLE [32].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Ϫ607 A/C (rs1946518), Ϫ137 C/G (rs187238) in the promoter region, and Ϫ140 C/G (previously Ϫ133 C/G, rs4988359) in intron 1 have been studied in detail with respect to etiopathogenesis of allergic diseases [15][16][17][18] and transcriptional activity or IL-18 production by monocytes [19 -21]. Current results have indicated the inconsistent association between IL-18 gene variants and clinical/ intermediary phenotypes of allergy in different populations [15][16][17][18][22][23][24][25][26][27][28][29][30][31]. However, a novel putative functional variant Ϫ1297 C/T (rs360719) within the IL-18 promoter region that seems to have an important role in IL-18 expression was recently associated with susceptibility to SLE [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of these studies were incoherent. Many studied suggested that the IL-18 polymorphisms were associated with asthma, [10][11][12][13][14] whereas some studies indicated that lack of an association between IL-18 polymorphisms and asthma. 6,[15][16][17][18] The inconsistent results may result in a single study or small sample size makes the lower statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of the IL-18 -607 C allele was significantly higher in patients with COPD and was found to be associated with increased disease susceptibility and severity of airflow restriction in male smokers within the Chinese Han population, whereas no significant association between IL-18 G/C genotype was observed with COPD (Wang et al, 2013). The synonymous variation in IL-18 rs549908 (105A/C) has been investigated for its association with asthma in a Chinese population where patients carrying the C/C homozygous genotype at rs549908 were observed to have a higher risk of developing asthma than those carrying the IL18 105A/C genotype (Lee et al, 2008). The association of the -607C/A genotype in the promoter region of IL-18 with asthma has been assessed, and although the frequency of the -607AA genotype appeared to be higher in Egyptian asthmatic children, the association was not statically significant (Shaaban et al, 2014) (Table 3)…”
Section: Introductionmentioning
confidence: 99%